Artificial Intelligence (A.I) Application in Foreign Language Teaching and Learning - Nga, Pham Thanh (European Journal of Applied Sciences, 2022)
In this article, the author will analyze specifically the problem of using artificial intelligence (AI) technology in teaching Foreign Language at the higher education. From there, the author will propose some solutions to further improve the effectiveness of using AI technology in teaching and learning English in particular and foreign languages ​​in general in Vietnam in the next period.